دەركەوتنی دامەزراوە ئایینییەكانی كڵێسا و پاپەویەت لە ئایینی مەسیحیدا (موستەل) - اسماعيل, صلاح كانبى; میراحمد, غفور بارام (Sulaimani Journal for Humanities, 2022)
In this study, we referred to the emergence of religious institutions such as the church and the papacy, which have a special importance in the history of Christianity, and have played a role in preserving the identity of this religion. Despite all the obstacles and oppression faced by its followers, it was able to grow and spread throughout the empire. In the fourth century AD, the followers of this religion increased and became the only official religion of the political power of the empire. The administrative system of the church and the papacy tried to control the world power in order to unite the churches and compete with the empire and its authority in order to achieve this goal. Our study consists of two sections. The first topic: under the title of the church as a religious and political institution, the second topic: the emergence of the papacy.